RELATIONSHIPS BETWEEN MARKET ORIENTATION, NON-TECHNOLOGICAL INNOVATION, AND BUSINESS PERFORMANCE AT SMALL AND MEDIUM INDUSTRIES (SMI) - Achmad, Lukman (Universitas Brawijaya, Indonesia, 2017)
This study aimed to examine the relationship between market orientation and business performance and mediated by non-technological innovation. This study uses a survey involving 71 companies producing automotive components. All companies are located in the district of Bandung, West Java, Indonesia. Data were analyzed using covariance-based structural equation modeling. The results showed that the orientation of the market is very important to improve the performance of the business and non-technological innovation capability. This study highlights the importance of the mediating role of non-technological innovation when examining the relationship between market orientation and business performance. The results imply that the company producing automotive components need to encourage them to increase the market orientation of non-technological innovation and business performance.